Participatory Monitoring & Evaluation: Learning from change - and Guijt, Irene; Gaventa, John (IDS, 1998)
Development organisations need to know how effective their efforts have been. But who should make these judgements, and on what basis? Usually it is outside experts who take charge. Participatory monitoring and evaluation (PM&E) is a different approach which involves local people, development agencies, and policy makers deciding together how progress should be measured, and results acted upon. It can reveal valuable lessons and improve accountability. However, it is a challenging process for all concerned since it encourages people to examine their assumptions about what constitutes progress, and to face up to the contradictions and conflicts that can emerge.